FIBRINOGEN DAN TRANSCRANIAL DOPPLER DI STROK ISKEMIK AKUT (Fibrinogen and Transcranial Doppler in Acute Ischemic Stroke) - Hafizah Soraya Dalimunthe; Adi Koesoema Aman; Yuneldi Anwar (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Elevated fibrinogen levels is related to the blood hyperviscosity, that causes low blood velocity. Non-contrast-enhanced transcranialDoppler (TCD) is used to evaluate blood flow from the cerebrovascular system. To know the relationship between fibrinogen levels andexamination of TCD in acute ischemic stroke through evaluation. A cross sectional study was admitted from July 2012-Juny 2013.The researchers determined the differences between fibrinogen and TCD in the stroke group and control. The researchers examinedthe relationship between fibrinogen and TCD examination in the stroke group. The fibrinogenwas measured with Clauss method. TheTCD was examined due to middle of the cerebral artery (MCA) and the Internal Carotid one Artery (ICA). The patients were diagnosedas ischemic stroke from head CT-scan. Statistical analyses employed the Independent T test, Anova test and Pearson correlation. Theresearchers had 24 patients and 24 controls that the Fibrinogen levels in stroke group is 549.16±104.84 mg/mL and in the control groupis 385.64±16.80 mg/mL. The researchers examined MCA in the stroke as well as the control and found the mean velocity 43.12±21.03and 56.97±6.22 (p=0.05), the peak velocity 74.17±32.58 and 94.55±14.11 (p=0.05) end diastolic velocity 23.27±12.66 and35.30±7.34 (p=0.00). In ICA, the stroke group and control and found the mean velocity 31.40±8.86 and 43.07±8.06 (p=0.00), thepeak velocity 54.99±11.50 and 75.04±16.04 (p=0.00) end diastolic velocity 18.23±7.67 and 25.64±5.24 (p=0.00). The correlationbetween fibrinogen and TCD in the stroke group was not significant on MCA and ICA, P>0.05. It can be concluded that the differencesbetween fibrinogen levels and TCD in the stroke group and control are significant. But there is no correlation between the fibrinogenand TCD in the stroke group.